Enhanced oxidation resistance of polyphenylene sulfide using organic–inorganic composite antioxidant via melt blending - Jian Xing; Rongnan Li; Zhenzhen Xu; Chunhong Zhu; Qingqing Ni (Polymer Testing)
Polyphenylene sulfide (PPS) has become the primary material for controlling gas emissions at high-temperature; however, the oxidation reactions of sulfur within PPS macromolecules can deteriorate the mechanical properties. In this study, to enhance the oxidation resistance of PPS, composite antioxidants were introduced. Composite antioxidants (GO-sHP) were prepared by chemically grafting semi-hindered phenol antioxidants (sHP) onto graphite oxide (GO) layers and then melt-blending them with PPS resin. The grafting of sHP onto the GO surface was achieved through esterification, which enhanced the thermal stability of GO. The resulting GO-sHP exhibited partial exfoliation and a uniform distribution within the PPS matrix. Owing to heterogeneous nucleation, the introduction of GO-sHP significantly enhanced the crystallinity (from 24.4 % to 59.9 %), crystal perfection and tensile properties (from 88.25 MPa to 97.55 MPa) of PPS. The thermal decomposition residue of PPS increased from 45.1 % to 50.8 % and the dynamic oxidation induction temperature of PPS was also significantly improved (increased by 18.1 °C) by the addition of GO-sHP. Moreover, lower chromatic value changes (from 8.25 to 0.95), higher tensile strength retention (from 94.59 % to 98.57 %) and greater C–S bond content (from 10.9 % to 54.4 %) were achieved after oxidation treatment. Additionally, the antioxidative mechanism of GO-sHP on PPS revealed that GO-sHP inhibits the formation of S=O bonds, retards the breakage of C–S bonds, eliminates the oxidative free radicals, and restricts the diffusion of free radicals and oxidizing substances within the PPS matrix.